2021
DOI: 10.3390/jcm10112378
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels in COVID-19 Outpatients from Western Mexico: Clinical Correlation and Effect of Its Supplementation

Abstract: Background: The immunomodulatory effects of vitamin D are known to be beneficial in viral infections; it is also known that its deficiency is associated with a prognosis more critical of Coronavirus Disease 2019. This study aimed to determine baseline vitamin D serum concentrations and the effects of its supplementation in asymptomatic or mildly symptomatic Coronavirus Disease 2019 outpatients. Methods: 42 outpatients were included, 22 of which received a supplement of 10,000 IU of vitamin D3 for 14 days; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 52 publications
(69 reference statements)
1
50
0
2
Order By: Relevance
“…Of the 13 studies, 10 were observational studies [7-10, 12-14, 22-24], while 3 were RCTs [11,15,25]. Relevant studies where clinical outcomes were not reported in terms of ICU admission or mortality were excluded [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 studies, 10 were observational studies [7-10, 12-14, 22-24], while 3 were RCTs [11,15,25]. Relevant studies where clinical outcomes were not reported in terms of ICU admission or mortality were excluded [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed 755 articles for eligibility, 6 RCTs [14][15][16][17][18][19] comprising 551 COVID-19 patients were selected for final analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…There were two multi-center [16,18] and four single center RCTs [14,15,17,19], one doubleblinded [16] and four registered clinical trials [14][15][16]18]. Vitamin D treatment was compared to placebo in two studies [16,17], non-vitamin control in three studies [14,15,19], and standard treatment comparator group in one study [18]. While Castillo et al [14] used calcifediol with an allocation ratio of 2:1; all other studies used cholecalciferol with an allocation ratio of 1:1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations